2013
DOI: 10.1136/thoraxjnl-2013-203775
|View full text |Cite
|
Sign up to set email alerts
|

Lung imaging during acute chest syndrome in sickle cell disease: computed tomography patterns and diagnostic accuracy of bedside chest radiograph

Abstract: IntroductionThe lung computed tomography (CT) features of acute chest syndrome (ACS) in sickle cell disease patients is not well described, and the diagnostic performance of bedside chest radiograph (CR) has not been tested. Our objectives were to describe CT features of ACS and evaluate the reproducibility and diagnostic performance of bedside CR. Methods We screened 127 consecutive patients during 166 ACS episodes and 145 CT scans (in 118 consecutive patients) were included in the study. Results Among the 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 33 publications
2
36
1
Order By: Relevance
“…7 Each lung was divided into 6 regions (the upper and lower parts of the anterior, lateral, and posterior regions), using a cephalocaudal mid-axillary line and a transversal hilar line for delineation, and the apex, mediastinum border, diaphragm, and external limit of the rib cage as external landmarks, as previously described. 12 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Each lung was divided into 6 regions (the upper and lower parts of the anterior, lateral, and posterior regions), using a cephalocaudal mid-axillary line and a transversal hilar line for delineation, and the apex, mediastinum border, diaphragm, and external limit of the rib cage as external landmarks, as previously described. 12 …”
Section: Methodsmentioning
confidence: 99%
“…7 The 12 lung regions that were explored by LU and CT were also analyzed using CR, using the same anatomic landmarks (apex, mediastinum border, diaphragm, external limit of the rib cage, mid-axillary line, and transversal hilar line), with posterior lung regions being defined as those with radiologic signs erasing the mediastinum border (“silhouette sign”), as previously described. 12 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute chest syndrome in SCD comes in many radiographic forms. Mekontso Dessap et al 19 found that consolidation was more severe in the apex and was more prevalent than ground glass change or atelectasis. Its presence was associated with a worse prognosis.…”
Section: Paediatric Year In Reviewmentioning
confidence: 99%
“…While discussing our paper,2 the reviewer seems to have misinterpreted our results when saying that consolidation is more severe in the apex of adult sickle cell disease patients with acute chest syndrome. In fact, CT and bedside chest radiography showed that lung parenchyma was increasingly consolidated from apex to base 2. This distribution is in accordance with previous studies,3 4 but may vary with age, with young children having more upper and middle lobe disease, contrarily to adult patients 3…”
mentioning
confidence: 99%